Semidiscretization in Space of Nonlinear Degenerate Parabolic Equations with Blow-up of the Solutions (Journal of Computational Mathematics, 2021)
Semidiscretization in space of nonlinear degenerate parabolic equations of nondivergent form is presented, under zero Dirichlet boundary condition. It is shown that semidiscrete solutions blow up in finite time. In particular, the asymptotic behavior of blowing-up solutions, is discussed precisely.